Platicrista horribilis, a new species of Tardigrada (Eutardigrada: Hypsibiidae) from Mongolia - Kaczmarek, ŁUkasz; Michalczyk, Łukasz (Zootaxa, 2003)
A new eutardigrade, Platicrista horribilis sp. nov., is described from moss samples collected in Mongolia. This species differs from others of genus Platicrista mainly by having indented lunules on the IV pair of legs.